Behaviour of cellular materials under impact loading - Vesenjak, M.; Ren, Z.; Ochsner, Andreas (Wiley-Vch, 2008)
The paper describes experimental and computational testing of regular open-cell cellular structures behaviour under impact loading. Open-cell cellular specimens made of aluminium alloy and polymer were experimentally tested under quasi-static and dynamic compressive loading in order to evaluate the failure conditions and the strain rate sensitivity. Additionally, specimens with viscous fillers have been tested to determine the increase of the energy absorption due to filler effects. The tests have shown that brittle behaviour of the cellular structure due to sudden rupture of intercellular walls observed in quasi-static and dynamic tests is reduced by introduction of viscous filler, while at the same time the energy absorption is increased. The influence of fluid filler on open-cell cellular material behaviour under impact loading was further investigated with parametric computational simulations, where fully coupled interaction between the base material and the pore filler was considered. The explicit nonlinear finite element code LS-DYNA was used for this purpose. Different failure criteria were evaluated to simulate the collapsing of intercellular walls and the failure mechanism of cellular structures in general. The new computational models and presented procedures enable determination of the optimal geometric and material parameters of cellular materials with viscous fillers for individual application demands. For example, the cellular structure stiffness and impact energy absorption through controlled deformation can be easily adapted to improve the efficiency of crash absorbers.